PENGARUH KOMPENSASI FINANSIAL TERHADAP KINERJA KARYAWAN KOPERASI KONSUMEN TIRTA KANDILO KABUPATEN PASER - Latte, Jumai (Inovatif Jurnal Administrasi Niaga, 2023)
The purpose of this research is to determine the effect of financial compensation on the performance of employees of the Tirta Kandilo Consumer Cooperative. The type of research is explanatory. The population and samples in this research are all Tirta Kandilo Consumer Cooperatives with a total sample of 47 employees using the accidental sampling technique. The data analysis technique in this research used statistical SPSS 21.0 software for Windows. Based on the results of calculation and analysis that have been made in this research proves that financial compensation (X) has a Sigma value 0.000 < 0,05 (Less than 0.05) and judging from the comparison of the value of Tcalculate > Ttable in the significance level of 5% is 8355> 2412. As Sigma X (financial compensation) below 0.05 and Tcalculate > Ttable, then Ho is rejected and Ha is accepted which means that financial compensation is significantly affect on employee performance of Tirta Kandilo Customer Cooperatives Paser Regency. The amount of influence is 78.0% known from the standard Coefficient Beta. Meanwhile, 22.0% is an influence of other variables that are not studied in this research.